Consequences of the new competition rules for the high jump at the European Team Championships - Theodorou, A.; Skordilis, E. (New Studies in Athletics, 2009)
In 2009 European Athletics replaced the European Cup with the European Team Championships. The new event featured innovative technical rule changes in many events including the pole vault and high jump, where each competitor was entiteled to a maximum of four aggregate fouls throughout the competition. The purpose of this study was to examine the effects of the new rules on performances in the high jump. Data on performances in the top leagues (n = 48; 24 males and 24 females) were obtained from both the 2008 European Cup and the 2009 European Team Championships. Nine dependent variables were examined using a statistical analysis package. The authors found the new rules had not effect the results but, in the case of male jumpers, several performances parameters including mean height and the number of succesful attempts had improved. They suggest a psycholigical effect of the rules that was to make the jumpers more focused on their technique. On the other hand, the overall performance of the women jumpers seems to have deterioritated. The number of attempts taken and the mean mark achieved were lower and there were more failed efforts in 2009 compared to 2008. A possible explanation is that the pschological effect led to the jumpers taking too few attempts and failing more often.